Poly-Arginine and Arginine-Rich Peptides are Neuroprotective in Stroke Models. Issue 6 (June 2015) - Meloni, Bruno P; Brookes, Laura M; Clark, Vince W; Cross, Jane L; Edwards, Adam B; Anderton, Ryan S; Hopkins, Richard M; Hoffmann, Katrin; Knuckey, Neville W
Using cortical neuronal cultures and glutamic acid excitotoxicity and oxygen-glucose deprivation (OGD) stroke models, we demonstrated that poly-arginine and arginine-rich cell-penetrating peptides (CPPs), are highly neuroprotective, with efficacy increasing with increasing arginine content, have the capacity to reduce glutamic acid-induced neuronal calcium influx and require heparan sulfate preotoglycan-mediated endocytosis to induce a neuroprotective effect. Furthermore, neuroprotection could be induced with immediate peptide treatment or treatment up to 2 to 4 hours before glutamic acid excitotoxicity or OGD, and with poly-arginine-9 (R9) when administered intravenously after stroke onset in a rat model. In contrast, the JNKI-1 peptide when fused to the (non-arginine) kFGF CPP, which does not rely on endocytosis for uptake, was not neuroprotective in the glutamic acid model; the kFGF peptide was also ineffective. Similarly, positively charged poly-lysine-10 (K10) and R9 fused to the negatively charged poly-glutamic acid-9 (E9) peptide (R9/E9) displayed minimal neuroprotection after excitotoxicity. These results indicate that peptide positive charge and arginine residues are critical for neuroprotection, and have led us to hypothesize that peptide-induced endocytic internalization of ion channels is a potential mechanism of action. The findings also question the mode of action of different neuroprotective peptides fused to arginine-rich CPPs.